Gender matters in global politics a feminist introduction to international relations - Shepherd, Laura J.; Hamilton, Caitlin (Routledge, Taylor & Francis Group, 2023)
"Gender Matters in Global Politics is a comprehensive textbook for advanced undergraduates studying politics, international relations, development, and similar courses. It provides students with an accessible but in-depth account of feminist methodologies, gender theory, and feminist approaches to key topics and themes in global politics. This textbook is written by an international line-up of established and emerging scholars from a range of theoretical perspectives, bringing together cutting-edge feminist scholarship in a variety of areas. This fully revised and updated third edition: Introduces students to feminist and gender theory and explains the relevance to contemporary global politics; Explains the insights of feminist theory for a range of fields of study, including international relations, international political economy, and security studies; Presents feminist approaches to key contemporary issues such as climate change, digital politics, war and militarism, disability, and global health; and Features pedagogical tools and resources including discussion questions, suggestions for further reading, and online resources. This text enables students to develop a sophisticated understanding of the work that gender does in policies and practices of global politics. The companion website for this book can be found at: https://routledgetextbooks.com/textbooks/9780367477608"--